Melanocarcinoma amelanico perianal. Case presentation - Juan E. Domínguez Suárez; Bárbara Lucía Cabezas Poblet; Rubén Bembibre Taboada (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
The malignant melanoma is a neoplasia that originates from melanocites. Its uncontrolled growing is manifested initially as a macula that, while evolutioning, conforms a strongly pigmented tumor, at times ulcerated and hemorrhaged, that tends to grow progressively in size, it has a high metastatic potential and an unfavorable prognosis. In this work, a case evaluated in the Coloproctology Service of the Universitary Hospital ¨Dr. Gustavo Aldereguia Lima¨, of Cienfuegos, is exposed, corresponding to an 87 year old female patient, with an exuberant perianal lesion, submitted to surgical intervention to better her life quality. Based in the histopathological study, it was diagnosed as melanocarcinoma.